JEJAK SYIAH DALAM KESENIAN TABOT BENGKULU; SUATU TELAAH SEJARAH - Lesi Maryani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2018)
Islam Nusantara is the one of many various Islamic paradigm in this world. This islamic expression tends on values and cultural structures of tradition that existed in Nusantara. One of the best way to study that case depicts in Tabot of City of Bengkulu. This cultural product is the result of the struggle of Islam and local culture. This celebration was held to remember the death of Sayyidina Husein, grandson of Muhammad SAW who died in Karbala. Shia sect is the one of the islamic sect that flourished in Indonesia. In it’s development, Shia element also adds many Islamic ritual in Nusantara. Nusantara’s Shia is not the same as the one in the middle east. In this archipelago, Shia melt in the general islamic view that called Ahlussunnah wal Jamaah. That phenomena can be seen in tabot celebration, where people are in it doet not have the Shia